2023
DOI: 10.3892/or.2023.8523
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‑10b‑5p facilitates the proliferation of uterine leiomyosarcoma cells: A microRNA sequencing‑based approach

Abstract: Uterine leiomyosarcoma (ULMS) is one of the most aggressive gynecological malignancies. In addition, the molecular background of ULMS has not been fully elucidated due to its low incidence. Therefore, no effective treatment strategies have been established based on its molecular background. The present study aimed to investigate the roles of microRNAs (miRNAs/miRs) in the development of ULMS. Comprehensive miRNA sequencing was performed using six ULMS and three myoma samples, and revealed 53 and 11 significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…According to previous papers (4950), comprehensive miRNA sequencing was performed. Sample EVs were isolated from MCF-7 cells, MCF-7 PSAT1 OE cells, BM02 cells and BM02 PSAT1 KD cells.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous papers (4950), comprehensive miRNA sequencing was performed. Sample EVs were isolated from MCF-7 cells, MCF-7 PSAT1 OE cells, BM02 cells and BM02 PSAT1 KD cells.…”
Section: Methodsmentioning
confidence: 99%
“…Among them, the function of several miRNAs in uLMS has been characterized. miR-10b-5p significantly inhibited cell proliferation, reduced the number of colonies, and increased the number of uLMS cells in the G1 phase [145]. miR-130b promoted aggressiveness in LMS cells by accelerating tumor growth and enhancing metastatic potential [150].…”
Section: Non-coding Rnamentioning
confidence: 96%
“…Among several types of non-coding RNAs, intercellular miRNAs have been extensively investigated and demonstrated their important roles in cell signaling, proliferation, migration, and angiogenesis in LMS development [144] (Table 4). A few comparison studies between myometrium and LMS at tissue and cell levels identified many differentially expressed miRNAs [145][146][147][148][149]. Among them, the function of several miRNAs in uLMS has been characterized.…”
Section: Non-coding Rnamentioning
confidence: 99%